Prevalence and factors associated with early discontinuation rate of Implanon utilization among women who ever used Implanon in Kucha District Gamo Gofa Zone, Southern Ethiopia - Mamecha Mesha; Akalewold Alemayehu; Deresse Daka (BMC, 2020)
Abstract Background The promotion of contraception in countries with high birth rates has the potential to reduce poverty, hunger, maternal, and childhood deaths. Every year in sub-Saharan Africa approximately 14 million unintended pregnancies occurred and a sizeable proportion was due to poor use of short-term hormonal methods. Contraceptive hormonal implants are highly effective and suitable for almost all women at any stage of their reproductive lives. On the other hand, early discontinuation of the Implanon contraceptive method utilization is one of the foremost problems amid the family planning program. Early discontinuation of the Implanon contraceptive method and reasons for such discontinuation lingers the most significant anxiety for family planning programs. In unindustrialized countries, contraceptive discontinuation due to health concerns is generally higher; these complaints are often related to service quality. Hence, this study aimed to assess the prevalence and factors associated with early discontinuation of Implanon among women who ever used Implanon in Kucha district, Gamo Gofa Zone, Southern Ethiopia. Methods Implanon contraceptive device users were selected from the Kucha district using a cross-sectional community-based survey from January to March 2018. A total of 430 women were selected and data were collected through face-to-face interviews by using a pre-tested structured questionnaire. Data were cleaned, coded, and entered into Epi-Info version 7statistical software. Factors that showed association in a bivariate analysis that has a p value of less than 0.25 were entered into multiple logistic regression models for controlling confounding factors. The strength of statistical association was measured by adjusted odds ratio, at 95% confidence intervals, and p value < 0.05 were considered as statistically significant variables. Result The result of this study revealed that the overall discontinuation rate of Implanon in the study was 34%. Variables having statistically significant association with Implanon discontinuation were women who never use a contraceptive method other than Implanon (AOR = 2.96, 95% CI 1.53-5.74), women who didn't make discussion with a partner (AOR = 3.32, 95% CI 1.57-7.04), poor counseling and follow up (AOR = 9.23, 95% CI 4.7-18.13), fear of side effects (AOR = 0.12, 95% CI 0.058- 0.24) and poor satisfaction of service (AOR = 5.2, 95% CI 2.77- 9.76) Conclusion The overall early discontinuation rate of Implanon in the study area was high. The main factors associated with early discontinuation of Implanon were contraceptive ever use, discussion with partner, poor follow-up of counseling, fear of side effects, and un-satisfaction by the services given during the insertion rate of Implanon.